Legal Analysis of the Refusal of Medical Treatment Based on the Patient's Religious Beliefs - R.Pratama; S.Wijaya (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: The intersection of religious freedom and medical law presents a profound legal and ethical dilemma when a competent patient refuses life-saving medical treatment based on deeply held religious beliefs. This study analyzes the legal boundaries, human rights protections, and judicial conflicts arising from such refusals. Methods: This study employs a normative legal research methodology, examining statutory regulations, constitutional provisions, human rights conventions, and relevant judicial precedents. Results: The legal framework establishes that while the principle of patient autonomy and religious freedom is heavily protected under constitutional and international law, this right is not absolute and faces significant constraints when state interests, the preservation of life, and the protection of minors or vulnerable third parties are compromised. Discussion: The discussion synthesizes the doctrine of informed refusal, the right to bodily integrity, and the constitutional guarantee of religious liberty against the state's parens patriae doctrine and the medical profession’s ethical duty to preserve life, highlighting a significant literature gap regarding uniform global legal standards. Conclusions: Courts generally uphold the refusal of competent adults but consistently intervene to mandate treatment for minors, indicating that the right to religious refusal is limited by the state's compelling interest in preserving human life and public welfare.